Local human pressures influence gene flow in a hybridizing Daphnia species complex. (22nd January 2016) - Alric, B.; Möst, M.; Domaizon, I.; Pignol, C.; Spaak, P.; Perga, M.‐E.
Abstract: Anthropogenic environmental changes are considered critical drivers of the genetic structure of populations and communities through, for example, the facilitation of introgressive hybridization between syntopic species. However, the mechanisms by which environmental perturbations trigger changes in the genetic structure of populations and communities, such as the processes that determine the directionality of hybridization and patterns of mitochondrial introgression over many generations, remain largely unexplored. In this study, the changes in genetic structure of hybridizing members of the Daphnia longispina species complex were reconstructed over the last 100 years for three large temperate lakes under strong anthropogenic pressures via palaeogenetic analyses of resting egg banks. Drastic changes in the genetic structure of the Daphnia community, associated with hybridization events between D. longispina and D. galeata and subsequent introgression, were detected in Lakes Geneva and Bourget. In Lake Bourget, these changes were induced by the successful establishment of D. galeata with rising phosphorus levels and reinforced by the sensitivity of D. longispina to fish predation pressure. In Lake Geneva, the pattern of hybridization during eutrophication is more likely a function of the original taxonomic composition of the species complex in this lake. Lakes seem to require at least a meso‐oligotrophic status to allow D. galeata populations to establish and accordingly no D. galeata genotypes were found in the egg bank of oligotrophic Lake Annecy. In contrast to the generally assumed pattern of unidirectional hybridization in this species complex, bidirectional hybridization was recorded in Lakes Geneva and Bourget. Our results also demonstrate complex genetic trajectories within this species complex and highlight the irreversibility of changes in the genotypic architecture of populations driven by local human pressures. Finally, we show that extensive hybridization and introgression do not necessarily result in a large and homogenous hybrid swarm.